Pelatihan Myob Accounting pada UKM Mahasiswa Akuntansi AMIK Indonesia - Rusman; Al Cassany, Saluddin; Nurhayati (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2021)
A student activity unit is a place for students to develop the talents, interests, expertise of each student, and the ability to socialize with the outside world. So, a high GPA will not guarantee that students will get success. However, the social skills that have been obtained in participating in UKM are the most valuable thing and at the same time are the key to the success of students in facing the outside world. MYOB accounting is an accounting software required by companies that are integrated (integrated software). In detail, the problem to be solved in this Community Service activity is whether through this training will be able to improve the ability of accounting SMEs in running Myob?. This community service activity is intended for SMEs to overcome their obstacles in preparing company financial reports. Activities that have been carried out are in the form of training on the use of accounting system simulation tools for SMEs with as many as 20 participants from UKM. The next activity is the implementation of simulation tools and mentoring activities are carried out. The evaluation results conclude that the Utilization Index of the tools assessed by UKM managers which are calculated using the usefulness index results in a range of IKP values ​​of 89 in the range b + 4c £IKP <a. IKP is at this interval, which means that UKM managers state that accounting simulation tools are very useful to be applied in UKM.